Ultrasonic NDT on aluminum bars: An experimental performance comparison of excitation and processing techniques. (November 2018) - Bernieri, A.; Ferrigno, L.; Laracca, M.; Rasile, A.; Ricci, M.
Abstract: Aluminum bars are structural elements widely used in many application fields (industrial, aerospace, naval, automotive, etc.). For the security and reliability of the structures in which they are used, it is very important to detect possible defects before using them or during their operating life. The Ultrasonic Non-Destructive Testing (US-NDT) seems to be very attractive as a diagnostic solution both for the initial and during the in-use inspections. In the literature, there are many instrumental solutions that differ with regard to the type of ultrasonic excitation signal, the adopted signal filtering and the implemented diagnostic algorithm. In this paper, an experimental comparison of various US-NDT excitation, filtering and diagnostic techniques is proposed, with the aim of identifying a suitable combination of such solutions that allows the best defect detection and localization capability. The experimental analysis was carried out on several specimens of aluminum bars with known defects (thin crack and corrosive defects). The obtained results show that the reliability of the defect diagnosis is strictly related both to the combinations of excitation, conditioning and processing methods implemented and to the type of the defect and its position respect to the inspection instrument.